YmoA negatively controls the expression of insecticidal genes in Yersinia enterocolitica. Issue 2 (13th March 2014) - Starke, Mandy; Fuchs, Thilo M.
Summary Y ersinia enterocolitica is toxic towards invertebrates due to the presence of the toxin complex (tc) genes that are activated by the thermolabile regulator TcaR2. In the search for further regulatory factors involved in insecticidal gene expression, the modulator of yersinial virulence, YmoA, was identified to silence all tc genes of the Y. enterocolitica strain W22703 (biovar 2, serovar O:9). Using promoter fusions with the luciferase reporter, we found that the deletion of ymoA results in elevated transcription of tcaR1, tcaR2, tcaA, tcaB, tcaC, tccC1 and tccC2 at both 15°C and 37°C. Complementation by episomal ymoA significantly reduced tc gene expression, thus validating the inhibitory activity of YmoA on the production of insecticidal proteins. YmoA contributes to the binding properties of H‐NS to the tc promoters by forming a complex with this nucleoid‐associated protein, and this complex not only binds to the upstream regions of all tc genes, but also to intragenic sites of tcaA and tcaB that play an important role in controlling the expression of both genes. At low temperature, the intracellular amount of thermostable YmoA is not reduced, but the repressor is less functional. These data point to H‐NS/YmoA as an antagonist of the inducer TcaR2.